(untitled) (Scientific journal of the Fergana State University, 2025)
The activities performed by preschool children are not only carried out by the children themselves, but every conscious action is activated and controlled by the brain. The psychophysiological characteristics performed by the brain are certainly implemented in the process of preschool education from a neuro-pedagogical perspective. In the development of cognitive activity in preschool children, neuro-pedagogical opportunities are extremely important, as they help enhance brain development and make the learning process more effective. Neuro-pedagogy is a field that studies brain activity and its role in learning, and by applying this knowledge in the educational process, it is possible to optimize the cognitive development of children. Through neuropedagogy, it is possible to diagnose individual difficulties that arise in the intellectual development of the child and to correct them in accordance with the types of cranial hemispheres. This will allow the child to fully realize his potential. This article discusses the opportunities of neuro-pedagogy in the development of cognitive activity in preschool children.